Effect of Dietary Levels of Toasted Mucuna Seed Meal (TMSM) on the Performance and Egg Quality Parameters of Laying Japanese Quails (Coturnix coturnix japonica) - Tuleun , C.D.; Dashe, N.A. (International Journal of Poultry Science, 2010)
A 8 week feeding trial was conducted to determine the effect of dietary inclusion of Toasted Mucuna Seed Meal (TMSM) on the performance and egg qualities of Japanese quail layers. Four (4) isonitrogenous (20% cp) diets were formulated to contain toasted mucuna seed meal at 0, 5, 10 and 15%. Each of the dietary treatments was triplicated with 10 birds per replicate (making a total of 120 birds for the experiment) in a completely randomized design. The birds were offered feed and water ad libitum. The results showed that the quail layers fed up to 15% dietary levels of TMSM had percent hen-day and hen housed egg production, average feed intake, feed intake per egg production and feed intake per gram egg production values that were not statistically different (p>0.05) from those fed the 0% TMSM (control) diet. Albumen width and shell thickness were significantly (p<0.05) lowered by the increasing levels of TMSM, while egg circumference and all yolk parameters were not affected significantly (p>0.05). Dietary inclusion of TMSM at all levels reduced feed cost which was also reflected in feed cost per egg produced and feed cost per bird produced. Therefore the use of TMSM as a feed ingredient up to 15% level in quail layer diets is profitable, feasible and desirable.